Semi-empirical modelling of dust air explosion severity in the 20-L sphere: Application to biomass and coal dusts - Roberto Paredes; María Chiquito; Lina M. López; María-Pilar Martínez-Hernando; Dimitrios Pantelakis; Blanca Castells (Process Safety and Environmental Protection, 2026)

Chemical pollutant mixtures associated with metabolic health: Results from the European Health Examination Survey in Luxembourg - Jesús Martínez-Gómez; Giovana M. Ciprián; Gwenaëlle Le Coroller; Achilleas Pexaras; Rodrigo Fernández-Jiménez; Brice M.R. Appenzeller; Maria Ruiz-Castell (Science of The Total Environment, 2025)

P19-34 Ontogeny of Drug-Induced Steatosis: From Key Initiating Events to Disease Phenotypes - E. López-Pascual; M. Moreno-Torres; E. Moro; P. Soluyanova; A. Rapisarda; R. Ortega-Vallbona; E. Serrano-Candelas; R. Gozalbes; R. Jover; J.V. Castell (Toxicology Letters, 2025)

P19-31 Unraveling drug-induced hepatic steatosis: clinical sub-phenotypes, prognosis prediction and identification of high-concern drugs and hazardous chemical attributes - M. Moreno-Torres; E. López-Pascual; E. Moro; A. Rapisarda; B. Lindeman; A. Verhoeven; T. Luechtefeld; E. Serrano-Candelas; H. Dirven; J.V. Castell; R. Jover (Toxicology Letters, 2025)

Differential innate immune activation by four different CpG-ODNs in porcine and murine cells: Implications for vaccine design - Giuliana Vedelago; Luz M. Palacios; Sofía D. Castell; Constanza Marin; Federico N. Ruiz Moreno; M. Esperanza Felici; Nicolás D. Dho; Daniel A. Allemandi; Santiago D. Palma; Gabriel Morón; Fernando A. Bessone; Fabrisio E. Alustiza; et al. (Research in Veterinary Science, 2025)

Macroevolutionary Patterns of Phytochemical Diversity in a Macaronesian Archipelago - Xoaquín Moreira; Luis Abdala‐Roberts; Jonay Cubas; Beatriz Lago‐Núñez; Nereida M. Rancel‐Rodríguez; Cristina González‐Montelongo; Gaétan Glauser; Matthieu Bueche; Emmanuel Defossez; Juli Caujapé‐Castells; Víctor Bello‐Rodríguez; Juan José García‐Alvarado; et al. (Global Ecology and Biogeography, 2025)
Aim Plant specialised metabolites are highly diverse and serve various functions, yet the different forms of phytochemical complexity and their drivers are often not fully understood. In this context, islands provide a valuable opportunity to explore the drivers of phytochemical diversity and its adaptive significance, owing to their unique physical features and markedly different biotic and abiotic pressures compared to the mainland. Location Macaronesian region. Time Period Contemporary. Major Taxa Studied Vascular plants. Methods We investigated macroevolutionary patterns in the diversity of plant specialised chemistry by conducting metabolomic analyses of leaf samples from 54 species on the Canary Islands. Our goal was to determine whether the mean crown node age, which relates to a species' island residence time, influences phytochemical diversity. To gain mechanistic insight into selective abiotic pressures, we also examined whether temperature and precipitation, associated with species' climatic niches, affected phytochemical diversity. Results Crown age did not correlate with overall phytochemical diversity but did influence the production of specific metabolite groups, with some types of compounds showing a positive correlation and others a negative correlation with crown age. Temperature and precipitation played significant roles in shaping phytochemical diversity, with temperature having a negative influence and precipitation exerting a positive effect. Both climatic factors also affected the levels of specific compound groups, driving either an increase or decrease depending on the metabolite type. Main Conclusions Our findings reveal novel linkages between phytochemical diversity, climate and species residence time on islands, suggesting evolutionary processes that lead to divergent patterns of plant phytochemical complexity. Exploring these evolutionary mechanisms and the extent to which these patterns represent adaptive responses (e.g., to climate) can ccontribute to advancing our understanding of phytochemical variation.

Wastewater-Based Epidemiology for Analysis of Human Papillomavirus Infections in a Uruguayan Urban Area - C. Fernandez-Sabatella; G. Corrales; L. Monzon; E. Andrade; N. Sica; E. Cardozo; N. Baccardatz; J. Jacques; S. Castro; M. Castells; M. Victoria; R. Colina (Food and Environmental Virology, 2025)

The acyl glucuronide of 2-(4-diethylamino-2-hydroxybenzoyl)benzoic acid: Synthesis, structural assignment, occurrence as a human phase II metabolite of Uvinul® A Plus and acute aquatic toxicity - María Payá-García; Gemma M. Rodríguez-Muñiz; Marta Moreno-Torres; Erika Moro; Lucas Santos-Juanes; Ana M. Amat; Salvador Gil; José V. Castell; Virginie Lhiaubet-Vallet; Miguel A. Miranda (Chemosphere, 2025)

Last twenty-years activity of cardiovascular tissue banking in Barcelona - C. Castells-Sala; M. L. Pérez; E. Agustí; A. Aiti; E. Tarragona; A. Navarro; J. Tabera; O. Fariñas; J. L. Pomar; A. Vilarrodona (Cell and Tissue Banking, 2024)
The Barcelona Tissue Bank was established from the merge of two previous multi-tissue banks. Potential donors are screened by Donor Center staff and multi-tissue retrieval is performed by specialized own teams. Tissue processing and preservation is performed in clean room facilities by specialised personnel. After quality control of both donor and all tissues results, the heart valves and vascular segments are stored until medical request. The aim of this report is to present the cardiovascular tissue activity and retrospectively evaluate the outcomes of the changes performed in last 20 years. Cardiovascular tissue from 4088 donors was received, specifically 3115 hearts and 2095 vascular segments were processed and evaluated. A total of 48% of the aortic valves, 68% of the pulmonary valves and 75% of the vascular segments were suitable for transplant. The main reason for discarding tissue was macroscopic morphology followed by microbiological results, for both valves and arteries. Altogether, 4360 tissues were distributed for transplantation: 2032 (47%) vascular segments, 1545 (35%) pulmonary valves and 781 (18%) aortic valves. The most common indication for aortic valve surgery was the treatment of endocarditis, while for pulmonary valves, it was congenital malformation reconstruction. Vascular segments were mainly used for reconstruction after ischemia. During this period, a number of changes were made with the goal of enhancing tissue quality, safety and efficacy. These improvements were achieved through the use of a new antibiotic cocktail, increasing of donor age criteria and changing the microbiological control strategy.

P16-55: Using Metabolomics to Uncover Ontogeny of Drug-Induced Hepatotoxicity and Underlying AOP Mechanisms - T. Martinez-Sena; E. Moro; M. Moreno Torres; G. Quintas; J. Hengstler; R. Jover; J. V. Castell Ripoll (Toxicology Letters, 2023)

Capture of CO2 and Water While Driving for Use in the Food and Agricultural Systems - Maria A. Barrufet; Elena M. Castell-Perez; Rosana G. Moreira (Circular Economy and Sustainability, 2022)

The late Pleistocene endemicity increase hypothesis and the origins of diversity in the Canary Islands Flora - Juli Caujapé‐Castells; Carlos García‐Verdugo; Isabel Sanmartín; Javier Fuertes‐Aguilar; Maria M. Romeiras; Nieves Zurita‐Pérez; Rafael Nebot (Journal of Biogeography, 2022)
Aim We explore the idea that most pre‐glacial non‐endemic Canarian flora became endemic to the archipelago by the extinction of its mainland populations during the late Pleistocene glaciations, implying that the extant non‐endemic flora is mostly post‐glacial: the ‘late Pleistocene endemicity increase hypothesis’. Taxon The native flora of the Canarian archipelago. Methods We statistically compare the distributions of 2087 Canarian endemic and native non‐endemic plants across islands. We also carry out connectivity analyses using their dispersal paths, obtained by connecting all the islands of occurrence for each taxon. Results While the distribution of the endemic flora is strongly L‐shaped (with a much higher proportion of Single‐Island Endemics than Multiple‐Island Endemics), that of the native non‐endemics is U‐shaped (i.e. similar prevalence of single‐island taxa and taxa distributed on all islands). The native non‐endemics have a significantly lower proportion of single‐island taxa and a higher proportion of widespread taxa than the endemics. Most dispersal paths in the endemics connect the central and western islands, whereas they are extended across all islands in the native non‐endemics. Main conclusions The contrasting distributional patterns of the endemics and the native non‐endemics support an outstanding role of species diversification in the endemic flora, but a still negligible influence of the insular selective and stochastic pressures (including extinction) in the native non‐endemic flora, arguably due to its recent origin. Our results suggest that the high endemicity levels of the extant Canarian flora can be explained by two complementary processes: (i) high diversification rates throughout the ontogeny of the archipelago, often from colonisers that attained a widespread distribution prior to speciation, and (ii) an ‘endemicity increase’ during the late Pleistocene glaciations, whereby most of the pre‐glacial non‐endemic Canarian flora became endemic due to the extinction of its mainland conspecific populations, thus emphasising the role of the Canaries as climatic refugia.

The in vitro assessment of the toxicity of volatile, oxidisable, redox-cycling compounds: phenols as an example - Laia Tolosa; Teresa Martínez-Sena; Johannes P. Schimming; Erika Moro; Sylvia E. Escher; Bas ter Braak; Bob van der Water; M. A. Miranda; Barbara M. A. van Vugt-Lussenburg; José V. Castell (Archives of Toxicology, 2021)
Phenols are regarded as highly toxic chemicals. Their effects are difficult to study in in vitro systems because of their ambiguous fate (degradation, auto-oxidation and volatility). In the course of in vitro studies of a series of redox-cycling phenols, we found evidences of cross-contamination in several in vitro high-throughput test systems, in particular by trimethylbenzene-1, 4-diol/trimethylhydroquinone (TMHQ) and 2,6-di-tertbutyl-4-ethylphenol (DTBEP), and investigated in detail the physicochemical basis for such phenomenon and how to prevent it. TMHQ has fast degradation kinetics followed by significant diffusion rates of the resulting quinone to adjacent wells, other degradation products being able to air-diffuse as well. DTBEP showed lower degradation kinetics, but a higher diffusion rate. In both cases the in vitro toxicity was underestimated because of a decrease in concentration, in addition to cross-contamination to neighbouring wells. We identified four degradation products for TMHQ and five for DTBEP indicating that the current effects measured on cells are not only attributable to the parent phenolic compound. To overcome these drawbacks, we investigated in detail the physicochemical changes occurring in the course of the incubation and made use of gas-permeable and non-permeable plastic seals to prevent it. Diffusion was greatly prevented by the use of both plastic seals, as revealed by GC–MS analysis. Gas non-permeable plastic seals, reduced to a minimum compounds diffusion as well oxidation and did not affect the biological performance of cultured cells. Hence, no toxicological cross-contamination was observed in neighbouring wells, thus allowing a more reliable in vitro assessment of phenol-induced toxicity.

Validation of self-reported adherence in chronic patients visiting pharmacies and factors associated with the overestimation and underestimation of good adherence - C. Valdés y Llorca; Ernesto Cortés-Castell; J. M. Ribera-Casado; P. de Lucas-Ramos; L. M. de Palacio-Guerrero; F. Mugarza-Borqué; J. L. Casteig-Ayestarán; J. Díaz-Olmo; A. Casteig-Blanco; V. F. Gil-Guillén; M. Rizo-Baeza (European Journal of Clinical Pharmacology, 2020)

Modeling the Transport of Human Rotavirus and Norovirus in Standardized and in Natural Soil Matrix-Water Systems - P. Gamazo; M. Victoria; J. F. Schijven; E. Alvareda; L. F. L. Tort; J. Ramos; L. A. Lizasoain; G. Sapriza; M. Castells; L. Bessone; R. Colina (Food and Environmental Virology, 2020)

An extensive field study reveals the circulation of new genetic variants of subtype 1a of bovine viral diarrhea virus in Uruguay - L. Maya; M. Macías-Rioseco; C. Silveira; F. Giannitti; M. Castells; M. Salvo; R. Rivero; J. Cristina; E. Gianneechini; R. Puentes; E. F. Flores; F. Riet-Correa; et al. (Archives of Virology, 2020)

Prediction of human drug-induced liver injury (DILI) in relation to oral doses and blood concentrations - Wiebke Albrecht; Franziska Kappenberg; Tim Brecklinghaus; Regina Stoeber; Rosemarie Marchan; Mian Zhang; Kristina Ebbert; Hendrik Kirschner; Marianna Grinberg; Marcel Leist; Wolfgang Moritz; Cristina Cadenas; et al. (Archives of Toxicology, 2019)

Biogeochemical recuperation of lowland tropical forest during succession - Benjamin W. Sullivan; Rachel L. DuBose; Megan K. Nasto; Silvia Alvarez‐Clare; Camie M. Dencker; Fiona M. Soper; Kevin T. Shoemaker; F. Yoko Ishida; Joana Zaragoza‐Castells; Eric A. Davidson; Cory C. Cleveland (Ecology, 2019)
High rates of land conversion and land use change have vastly increased the proportion of secondary forest in the lowland tropics relative to mature forest. As secondary forests recover following abandonment, nitrogen (N) and phosphorus (P) must be present in sufficient quantities to sustain high rates of net primary production and to replenish the nutrients lost during land use prior to secondary forest establishment. Biogeochemical theory and results from individual studies suggest that N can recuperate during secondary forest recovery, especially relative to P. Here, we synthesized 23 metrics of N and P in soil and plants from 45 secondary forest chronosequences located in the wet tropics to empirically explore (1) whether there is a consistent change in nutrients and nutrient cycling processes during secondary succession in the biome; (2) which metrics of N and P in soil and plants recuperate most consistently; (3) if the recuperation of nutrients during succession approaches similar nutrient concentrations and fluxes as those in mature forest in ~100 yr following the initiation of succession; and (4) whether site characteristics, including disturbance history, climate, and soil order are significantly related to nutrient recuperation. During secondary forest succession, nine metrics of N and/or P cycling changed consistently and substantially. In most sites, N concentrations and fluxes in both plants and soil increased during secondary succession, and total P concentrations increased in surface soil. Changes in nutrient concentrations and nutrient cycling processes during secondary succession were similar whether mature forest was included or excluded from the analysis, indicating that nutrient recuperation in secondary forest leads to biogeochemical conditions that are similar to those of mature forest. Further, of the N and P metrics that recuperated, only soil total P and foliar δ 15 N were strongly influenced by site characteristics like climate, soils, or disturbance history. Predictable nutrient recuperation across a diverse and productive ecosystem may support future forest growth and could provide a means to quantify successful restoration of ecosystem function in secondary tropical forest beyond biomass or species composition.

Long-term and mechanistic evaluation of drug-induced liver injury in Upcyte human hepatocytes - Laia Tolosa; Nuria Jiménez; María Pelechá; José V. Castell; Mª José Gómez-Lechón; M. Teresa Donato (Archives of Toxicology, 2019)

Evaluation of Bacterial Contamination as an Indicator of Viral Contamination in a Sedimentary Aquifer in Uruguay - P. Gamazo; M. Victoria; J. F. Schijven; E. Alvareda; L. F. L. Tort; J. Ramos; L. Burutaran; M. Olivera; A. Lizasoain; G. Sapriza; M. Castells; R. Colina (Food and Environmental Virology, 2018)

A model-based assay design to reproduce in vivo patterns of acute drug-induced toxicity - Lars Kuepfer; Olivia Clayton; Christoph Thiel; Henrik Cordes; Ramona Nudischer; Lars M. Blank; Vanessa Baier; Stephane Heymans; Florian Caiment; Adrian Roth; David A. Fluri; Jens M. Kelm; et al. (Archives of Toxicology, 2018)

Customised in vitro model to detect human metabolism-dependent idiosyncratic drug-induced liver injury - Laia Tolosa; Nuria Jiménez; Gabriela Pérez; José V. Castell; M. José Gómez-Lechón; M. Teresa Donato (Archives of Toxicology, 2018)

The loss of dispersal on islands hypothesis revisited: Implementing phylogeography to investigate evolution of dispersal traits in Periploca (Apocynaceae) - C. García‐Verdugo; M. Mairal; P. Monroy; M. Sajeva; J. Caujapé‐Castells (Journal of Biogeography, 2017)
Aim The loss of dispersal on islands hypothesis ( LDIH ) posits that wind‐dispersed plants should exhibit reduced dispersal potential, particularly if island populations are old. In this study, we tested this hypothesis using a detailed phylogeographical framework across different geographical scales. Location Mainland and island areas of the Atlantic and Mediterranean regions, including Macaronesia (Canary Islands and Cape Verde) and Mediterranean islands in the strait of Sicily. Methods Forty‐five populations of Periploca laevigata , a wind‐dispersed shrub, were sampled. Plastid and nuclear microsatellite data were used to reconstruct spatio‐temporal patterns of island colonization, and estimates of seed terminal velocity used as a surrogate for dispersal ability under both field and common garden conditions. Results Our findings did not provide evidence of loss of dispersability in any island lineage. In all of the regions considered, dispersal ability was similar on island and mainland populations, or higher on islands. Contrary to LDIH expectations, lineages inferred as the oldest (western Canaries and Cape Verde) converged towards the most dispersive seed phenotype. This pattern was supported by data obtained under common garden conditions. Within the western Canarian lineage, successful dispersal was shown to be very rare among islands and extensive within islands, but dispersability did not vary significantly from older to more recent sublineages. Considering all the study islands, we found a strong, positive correlation between dispersal ability and estimates of within‐island habitat availability. Main conclusions This study suggests that dispersal ability can be favoured on islands, possibly because traits enhancing wind dispersal are positively selected when habitat availability is high. Our results challenge broad generalizations of the LDIH , but we discuss how overlooking species′ phylogeographical history may give rise to misleading conclusions.

Discontinuation of pharmacological treatment of children and adolescents with attention deficit hyperactivity disorder: meta-analysis of 63 studies enrolling 11,788 patients - M. Riera; X. Castells; A. Tobias; R. Cunill; L. Blanco; D. Capellà (Psychopharmacology, 2017)

The photosynthetic cytochrome c 550 from the diatom Phaeodactylum tricornutum - Pilar Bernal-Bayard; Leonor Puerto-Galán; Inmaculada Yruela; Inés García-Rubio; Carmen Castell; José M. Ortega; Pablo J. Alonso; Mercedes Roncel; Jesús I. Martínez; Manuel Hervás; José A. Navarro (Photosynthesis Research, 2017)

Solar radiation and functional traits explain the decline of forest primary productivity along a tropical elevation gradient - Nikolaos M. Fyllas; Lisa Patrick Bentley; Alexander Shenkin; Gregory P. Asner; Owen K. Atkin; Sandra Díaz; Brian J. Enquist; William Farfan‐Rios; Emanuel Gloor; Rossella Guerrieri; Walter Huaraca Huasco; Yoko Ishida; et al. (Ecology Letters, 2017)
One of the major challenges in ecology is to understand how ecosystems respond to changes in environmental conditions, and how taxonomic and functional diversity mediate these changes. In this study, we use a trait‐spectra and individual‐based model, to analyse variation in forest primary productivity along a 3.3 km elevation gradient in the Amazon‐Andes. The model accurately predicted the magnitude and trends in forest productivity with elevation, with solar radiation and plant functional traits (leaf dry mass per area, leaf nitrogen and phosphorus concentration, and wood density) collectively accounting for productivity variation. Remarkably, explicit representation of temperature variation with elevation was not required to achieve accurate predictions of forest productivity, as trait variation driven by species turnover appears to capture the effect of temperature. Our semi‐mechanistic model suggests that spatial variation in traits can potentially be used to estimate spatial variation in productivity at the landscape scale.

Greenhouse gas calculator at farm level addressed to the growers - Carmen M. Torres; Assumpció Antón; Francesc Ferrer; Francesc Castells (The International Journal of Life Cycle Assessment, 2017)

Inter-laboratory study of human in vitro toxicogenomics-based tests as alternative methods for evaluating chemical carcinogenicity: a bioinformatics perspective - R. Herwig; H. Gmuender; R. Corvi; K. M. Bloch; A. Brandenburg; J. Castell; L. Ceelen; C. Chesne; T. Y. Doktorova; D. Jennen; P. Jennings; A. Limonciel; et al. (Archives of Toxicology, 2016)

High-content screening of drug-induced mitochondrial impairment in hepatic cells: effects of statins - Laia Tolosa; Antonio Carmona; José V. Castell; M. José Gómez-Lechón; M. Teresa Donato (Archives of Toxicology, 2015)

A single dose of a suicidal DNA vaccine induces a specific immune response in salmonids - M L Ogas Castells; J L La Torre; P R Grigera; T V Poggio (Journal of Fish Diseases, 2015)

Dietary intake of trace elements by the population of Catalonia (Spain): results from a total diet study - Gemma Perelló; Emilio Vicente; Victòria Castell; Juan M. Llobet; Martí Nadal; José L. Domingo (Food Additives & Contaminants: Part A, 2015)

Do island plant populations really have lower genetic variation than mainland populations? Effects of selection and distribution range on genetic diversity estimates - C. García‐Verdugo; M. Sajeva; T. La Mantia; C. Harrouni; F. Msanda; J. Caujapé‐Castells (Molecular Ecology, 2015)
Ecological and evolutionary studies largely assume that island populations display low levels of neutral genetic variation. However, this notion has only been formally tested in a few cases involving plant taxa, and the confounding effect of selection on genetic diversity ( GD ) estimates based on putatively neutral markers has typically been overlooked. Here, we generated nuclear microsatellite and plastid DNA sequence data in Periploca laevigata , a plant taxon with an island–mainland distribution area, to (i) investigate whether selection affects GD estimates of populations across contrasting habitats; and (ii) test the long‐standing idea that island populations have lower GD than their mainland counterparts. Plastid data showed that colonization of the Canary Islands promoted strong lineage divergence within P. laevigata , which was accompanied by selective sweeps at several nuclear microsatellite loci. Inclusion of loci affected by strong divergent selection produced a significant downward bias in the GD estimates of the mainland lineage, but such underestimates were substantial (>14%) only when more than one loci under selection were included in the computations. When loci affected by selection were removed, we did not find evidence that insular Periploca populations have less GD than their mainland counterparts. The analysis of data obtained from a comprehensive literature survey reinforced this result, as overall comparisons of GD estimates between island and mainland populations were not significant across plant taxa ( N = 66), with the only exception of island endemics with narrow distributions. This study suggests that identification and removal of markers potentially affected by selection should be routinely implemented in estimates of GD , particularly if different lineages are compared. Furthermore, it provides compelling evidence that the expectation of low GD cannot be generalized to island plant populations.

Human Health Risks Derived from Dietary Exposure to Toxic Metals in Catalonia, Spain: Temporal Trend - Gemma Perelló; Juan M. Llobet; Jesús Gómez-Catalán; Victòria Castell; Francesc Centrich; Martí Nadal; José L. Domingo (Biological Trace Element Research, 2014)

Development and characterization of nuclear microsatellite markers for Parolinia ornata Webb (Brassicaceae), and cross-species amplification in all species described in the Canarian endemic genus Parolinia - M. A. González-Pérez; J. Caujapé-Castells (Conservation Genetics Resources, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

A simple transcriptomic signature able to predict drug-induced hepatic steatosis - Marta Benet; Marta Moya; M. Teresa Donato; Agustín Lahoz; David Hervás; Carla Guzmán; M. José Gómez-Lechón; José Vicente Castell; Ramiro Jover (Archives of Toxicology, 2014)

Reduced seed predation after invasion supports enemy release in a broad biogeographical survey - Eva Castells; Maria Morante; José M. Blanco-Moreno; F. Xavier Sans; Roser Vilatersana; Anabel Blasco-Moreno (Oecologia, 2013)

Light inhibition of leaf respiration as soil fertility declines along a post-glacial chronosequence in New Zealand: an analysis using the Kok method - Owen K. Atkin; Matthew H. Turnbull; Joana Zaragoza-Castells; Nikolaos M. Fyllas; Jon Lloyd; Patrick Meir; Kevin L. Griffin (Plant and Soil, 2013)

HepG2 cells simultaneously expressing five P450 enzymes for the screening of hepatotoxicity: identification of bioactivable drugs and the potential mechanism of toxicity involved - Laia Tolosa; M. José Gómez-Lechón; Gabriela Pérez-Cataldo; José V. Castell; M. Teresa Donato (Archives of Toxicology, 2013)

Human Exposure to Arsenic, Cadmium, Mercury, and Lead from Foods in Catalonia, Spain: Temporal Trend - Isabel Martorell; Gemma Perelló; Roser Martí-Cid; Juan M. Llobet; Victoria Castell; José L. Domingo (Biological Trace Element Research, 2011)

Clinical characteristics and outcomes in familial adenomatous polyposis patients with a long-term treatment of celecoxib: a matched cohort study - Kui Huang; Lia P. Gutierrez; Steffen Bülow; Steven Gallinger; Antoni Castells; Craig J. Eagle; James M. Church (Familial Cancer, 2011)

Risk factors for multidrug-resistant Pseudomonas aeruginosa acquisition. Impact of antibiotic use in a double case–control study - M. Montero; M. Sala; M. Riu; F. Belvis; M. Salvado; S. Grau; J. P. Horcajada; F. Alvarez-Lerma; R. Terradas; M. Orozco-Levi; X. Castells; H. Knobel (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

PRI assessment of long-term changes in carotenoids/chlorophyll ratio and short-term changes in de-epoxidation state of the xanthophyll cycle - I. Filella; A. Porcar-Castell; S. Munné-Bosch; J. Bäck; M. F. Garbulsky; J. Peñuelas (International Journal of Remote Sensing, 2009)

Reduction of fumonisin B 1 in extruded corn breakfast cereals with salt, malt and sugar in their formulation - M. Castells; A.J. Ramos; V. Sanchis; S. Marín (Food Additives & Contaminants: Part A, 2009)

Dietary Intake of Arsenic, Cadmium, Mercury, and Lead by the Population of Catalonia, Spain - Roser Martí-Cid; Juan M. Llobet; Victoria Castell; José L. Domingo (Biological Trace Element Research, 2008)

Regulation of extracellular signal-regulated kinases (ERKs) by naloxone-induced morphine withdrawal in the brain stress system - Cristina Núñez; M. Teresa Castells; M. Luisa Laorden; M. Victoria Milanés (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Analysis of tropospheric ozone concentration on a Western Mediterranean site: Castellon (Spain) - Nuria Castell; Enrique Mantilla; Millan M. Millan (Environmental Monitoring and Assessment, 2007)

Effects of elevated plasma tryptophan on brain activation associated with the Stroop task - Rhian M. Morgan; Allyson M. M. Parry; Ricardo M. Arida; Paul M. Matthews; Bruce Davies; Linda M. Castell (Psychopharmacology, 2007)

Regulation of the kinase activity of the MIK GCK-like MAP4K by alternative splicing - Enric Castells; Pere Puigdomènech; Josep M. Casacuberta (Plant Molecular Biology, 2006)

Molecular evidence of hybridisation between the endemic Phoenix canariensis and the widespread P. dactylifera with Random Amplified Polymorphic DNA (RAPD) markers - M. A. Gonzlez-Prez; J. Caujap-Castells; P. A. Sosa (Plant Systematics and Evolution, 2004)

Salinity and Temperature Effects on the Lipid Composition of Mullet Sea Fry (Mugil cephalus, Linne, 1758) - S. Khériji; M. El Cafsi; W. Masmoudi; J.D. Castell; M.S. Romdhane (Aquaculture International, 2003)

Pharmacokinetic Behaviour of Albendazole Sulphoxide Enantiomers in Male and Female Sheep - B.P.S. Capece; G. Castells; F. Pérez; M. Arboix; C. Cristòfol (Veterinary Research Communications, 2000)

Cytochemical demonstration of modification of carbohydrates in the mouse zona pellucida during folliculogenesis - M. Avilés; M. El-Mestrah; L. Jaber; M. T. Castells; J. Ballesta; F. W. K. Kan (Histochemistry and Cell Biology, 2000)

The gp49A gene has extensive sequence conservation with the gp49B gene and provides gp49A protein, a unique member of a large family of activating and inhibitory receptors of the immunoglobulin superfamily - M. J. McCormick; M. C. Castells; K. F. Austen; H. R. Katz (Immunogenetics, 1999)

Responses of plasma glutamine, free tryptophan and branched-chain amino acids to prolonged exercise after a regime designed to reduce muscle glycogen - Cathy L. Zanker; Ian L. Swaine; Linda M. Castell; Eric A. Newsholme (European Journal of Applied Physiology, 1997)